When Bundism Expanded to the Americas: The Story of the Transnationalisation of Jewish Socialism (KULT_online, 2015)
Frank Wolff’s book tells a fascinating history of Bund, putting it in the context of migration and transnational exchanges. Basing his research on biographies of Bundist activist and numerous archival sources, the author underscores very personal aspects of modern political movements and shows how the Bundists truly dreamt about a better tomorrow that was supposed to happen “here and now”. For Wolff, the half-century long history of Bund serves as a departure point for examining how the movement evolved, transcended the geographical borders, and changed as its activists turned into migrants.